Antidiabetic and Antihypercholesterolemia Activities of Rambutan (Nephelium lappaceum L.) and Durian (Durio zibethinus Murr.) Fruit Peel Extracts - M. Muhtadi, H. Haryoto, Tanti Azizah Sujono, Andi Suhendi (Journal of Applied Pharmaceutical Science, 2016)
This research study aimed to explore the antidiabetic and antihypercholesterolemia activities of rambutan (Nephelium lappaceum L.) and durian (Durio zibethinus Murr.) fruit peels extracts. Diabetic rats induced by alloxan intra-peritoneal at dose 150 mg/kg.bw. Rats divided into eight groups, negative control received 0.5% CMC-Na, Glibenclamide 0.45 mg/kg.bw (positive control), groups of III, IV, and V were given ethanolic extracts of durian rind with successive doses of 500, 250, 125 mg/kg.bw, while groups of VI, VII and VIII were given of rambutan peels extracts for 11 days. Whereas, antihypercholesterolemia activity, high cholesterol gained by high-fat fed diet for 28 days and treated with the extracts for 14 days. The highest percentage reduction in blood glucose and cholesterol levels were shown of rambutan fruit peels extract with dose 500 mg/kg.bw and the value of percentage reduction were 61.76±4.26% and 60.75±8.26%, respectively which the activity were higher than positive control. While the durian rind extract with dose 500 mg/kg.bw had showed the reduction glucose levels at 50.19±3.66% and 35.82 ± 5.00% for reduction cholesterol levels. Nephelium lappaceum and Durio zibethinus peels extracts had the antidiabetic and antihypercholesterolemia activities at doses of 125 to 500 mg/kg.bw.
Keywords: Rambutan (Nephelium lappaceum L.), Durian (Durio zibethinus Murr.), antidiabetic, antihypercholesterolemia.